2005
DOI: 10.1007/s00595-004-3000-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hyperbaric Oxygen Treatment on the Renal Functions in Septic Rats: Relation to Oxidative Damage

Abstract: HBO treatment has a beneficial effect on renal dysfunction in sepsis. The probable reason for this effect is the reduction in oxidative damage because of the increase in antioxidative capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
6
22
0
Order By: Relevance
“…In our study, LPS treatment caused a time-dependent pronounced arterial hypotension that was associated with tachycardia and ARF with reduced GFR, indicating the validity of our sepsis model. Fractional sodium excretion and tubular sodium reabsorption, both indicators of tubular function in this study, decreased after LPS injection, indicating tubular damage, which is in accordance with previous findings (29,30). Noteworthy, it has been shown that LPS infusion had an immediate antinatriuretic effect in the first hours after injection, leading subsequently to a marked increase in fractional sodium excretion, suggesting a delayed LPS-induced impairment in tubular sodium reabsorption and therefore confirming our results (31).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, LPS treatment caused a time-dependent pronounced arterial hypotension that was associated with tachycardia and ARF with reduced GFR, indicating the validity of our sepsis model. Fractional sodium excretion and tubular sodium reabsorption, both indicators of tubular function in this study, decreased after LPS injection, indicating tubular damage, which is in accordance with previous findings (29,30). Noteworthy, it has been shown that LPS infusion had an immediate antinatriuretic effect in the first hours after injection, leading subsequently to a marked increase in fractional sodium excretion, suggesting a delayed LPS-induced impairment in tubular sodium reabsorption and therefore confirming our results (31).…”
Section: Discussionsupporting
confidence: 93%
“…Fractional excretion of glucose and tubular glucose reabsorption were indicators of tubular function in this study. Decreased tubular glucose reabsorption with resulting glucosuria indicated tubular damage during experimental inflammation, which is in accordance with findings of previous investigations regarding tubular sodium reabsorption (16,39).…”
Section: Discussionsupporting
confidence: 92%
“…A recent report clearly illustrated the therapeutic effects of HBO on attenuating sepsis-induced kidney injury [16]. However, the other recent report demonstrated that HBO alone did not sufficiently attenuate sepsis-induced liver injury [17].…”
Section: Introductionmentioning
confidence: 98%